HUBUNGAN KELELAHAN KERJA DENGAN KINERJA PERAWAT DALAM MELAKUKAN ASUHAN KEPERAWATAN PADA PASIEN COVID-19 DI RUANG ISOLASI RUMAH SAKIT ANANDA BEKASI - Hemi Afifah (2021)
Background: Performance is the result of a person's work both in quality and quantity individually. Fatigue can be interpreted as a condition of a person experiencing a decrease in work performance efficiency and a decrease in work strength and endurance in doing a job. Work fatigue that is not overcome will result in fatal work problems and result in work accidents. Objective: This research aims to determine whether there is a relationship between work fatigue and the performance of nurses in providing nursing care to COVID-19 patients in the Isolation Room of Ananda Hospital Bekasi. Method: This research used a descriptive-analytic research method with a cross-sectional approach and used a total sampling of 57 nurses as respondents. Result: A total of 49 nurses were female (86%). Most of the nurses in this research were <30 years old (87.7%). The results of the research concluded that there were 28 (49.1%) nurses experiencing work fatigue, while 29 (50.9%) nurses did not experience work fatigue. And the performance of nurses in the isolation room of Ananda Hospital Bekasi mostly had not good performance as many as 35 (61.4%), while 22 (38.6%) nurses had a good performance. The results of this research show a p-value = 0.019 which indicates that there is a significant relationship between work fatigue and the performance of nurses in the Isolation Room of Ananda Hospital Bekasi.